Horizontal and vertical distribution of sea lice larvae (Lepeophtheirus salmonis) in and around salmon farms in the Bay of Fundy, Canada. Issue 6 (21st November 2017) - Nelson, E J; Robinson, S M C; Feindel, N; Sterling, A; Byrne, A; Pee Ang, K
Abstract: The sea louse, Lepeophtheirus salmonis, is parasitic to salmonid species in the Northern Hemisphere and has become a widespread biological and economic problem for the salmon farming industry. A better understanding is needed of their spatial distribution and early life history to disrupt the life cycle of the sea louse. In this study, sea lice larval densities within salmon farms, between salmon farms and reference sites, and at various depths were quantified using both plankton pumps and plankton nets. Farm sites exhibited significantly higher densities than reference sites; however, these densities dropped an order of magnitude at a distance of 100 m from the cages. The majority of the larvae captured in the study were nauplii (93%), and densities ranged from 0 to 10 larvae/m 3 . Free‐swimming sea lice larvae were found to exhibit a diel cycle where nauplii larvae were in deeper waters (10–17 m) during the day and in surface waters (1–6 m) during the night. The results of this study suggest that the early life‐history stages of sea lice originate from and may remain close to active salmon farms, creating a self‐sustaining population.